Kajian Peningkatan Asam Lemak Omega-3 EPA dan DHA Pada Minyak Ikan Lele Yang Diberi Pakan Minyak Kacang Kedelai - Rosmawati Salasah; Mappiratu Mappiratu; Jusri Nilawati (Mitra Sains, 2016)
The experiment purpose to find out fatty acid profil in catfish oil were used soybean oil with different level and to detect soybean oil concentrate in dietary hight produce catfish oil contens omega-3 fatty acid EPA and DHA. This research uses experimental methods and experimental design used completely randomized design (CRD) with five treatments , the percentage giving linolenic acid in the feed catfish at A = 0 % , B = 5 % , C = 10 % , D = 15 % , and E 20 % with each of the three replicates (15 experimental units) . Data were analyzed statistically is the content of EPA and DHA oils catfish at each treatment . Catfish oil extraction is done by wet rendering . How to wet rendering applied to fish that are high in fat and in large numbers . Further fatty acid content is determined based on the area that is formed using a Gas Chromatography . Soy bean oil as a source of linolenic acid in the diet had no effect on oil fatty acid profile catfish (Clarias sp) in terms of the aspect of the type of fatty acids , but in terms of aspects of the concentration of each type of soybean oil fatty acids influence . Changes in fatty acid levels to concentrations of soybean oil are generally not patterned , the pattern follows the curve of a parabola and hyperbole, at concentrations of 0%, 5% trend fatty acid concentration increased until optimal at concentrations of 10% and at a concentration of 15 % and 20 % trend of concentration fatty acids then declined. Soybean oil concentration in the feed oil producing catfish containing omega-3 fatty acids , EPA and DHA concentration is highest at 10 % . Generated at these concentrations of omega - 3 fatty acids 8.33%, 5.05% EPA and DHA of 1.14 % .